2017
DOI: 10.1159/000455985
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of TRPC6 Signal Pathway Alleviates Podocyte Injury Induced by TGF-β1

Abstract: Background/Aims: Transforming growth factor beta 1 (TGF-β1) plays a critical role in the pathogenesis of glomerulosclerosis. The purpose of this study was to examine the effects of inhibition of transient receptor potential cation channel C6 (TRPC6) on podocyte injury induced by TGF-β1 via nephrin and desmin mechanisms. Methods: A rat model of nephropathy was first induced by intravenous injections of adriamycin to determine TRPC6 signal pathway engaged in glomerulosclerosis in vivo. Conditionally immortalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 45 publications
(42 reference statements)
2
25
0
Order By: Relevance
“…Our recent work has shown that nephrin is decreased whereas desmin is upregulated in injured podocyte induced by TGF-β1 [19], indicating that nephrin and desmin are involved in TGF-β1-induced podocyte injuries. Additionally, miR-155 is specifically localized in renal tissues and engaged in the pathogenesis of renal symptoms in patients with glomerulonephritis [26, 27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent work has shown that nephrin is decreased whereas desmin is upregulated in injured podocyte induced by TGF-β1 [19], indicating that nephrin and desmin are involved in TGF-β1-induced podocyte injuries. Additionally, miR-155 is specifically localized in renal tissues and engaged in the pathogenesis of renal symptoms in patients with glomerulonephritis [26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…in involvement of podocyte injury induced by TGF-β1 [16-18]. It should be noted that using a rat model with systemic injection of ADR, our recent study consistently observed that the higher protein expression levels of TGF-β1and apoptotic Caspase-9 in glomerular tissues, suggesting the role of TGF-β1 in the process of FSGS [19]. Nonetheless, it is significant to further determine the mechanisms leading to FSGS in renal diseases by using ADR-induced nephropathy.…”
Section: Introductionmentioning
confidence: 93%
“…TRPC6 signal plays a key role in mediating TGF-β1 induced podocyte injury via nephrin, desmin and caspase-9. [14] Pathway: GPCRs coupled to Gq signaling activate TRPC6, proposing that Gq-dependent TRPC6 stimulation underlies glomerular diseases [15] . Wnt/β-catenin signalling pathway may possibly be dynamic in pathogenesis of TRPC6-mediated diabetic podocyte injury [10] .…”
Section: Effect Of Trpc Activation: Trpc6 Channel Stimulation Increasmentioning
confidence: 99%
“…AS-IV may check HG-induced podocyte apoptosis via down regulation of TRPC6, which is maybe mediated via the calcineurin/NFAT signaling pathway [11] . Blockade of Wnt/β-catenin signalling by paricalcitol ameliorates proteinuria and kidney injury [18] Gq/TRPC6 signalling may have therapeutic benefits for the treatment of glomerular diseases [15] . Blocking TRPC6 signal pathway has a protective effect on podocyte injury [14] .…”
Section: Effect Of Trpc Activation: Trpc6 Channel Stimulation Increasmentioning
confidence: 99%
“…Thus, an impairment of any of their barrier functions following podocyte injury results in severe proteinuria and renal failure. Moreover, prolonged podocyte injury leads to glomerulosclerosis and progression of kidney disease [1][2][3][4][5]; however, the physiological regulation of podocytes and the pathological processes following injury are currently unclear.…”
Section: Introductionmentioning
confidence: 99%